Trich : a graphic novel on hair-pulling - Lim, Elizabeth Ying Ling (2017)
Trich is a graphic novel that aims to explore how illustration and narratives can highlight and communicate psychological, social and emotional concerns by a person with Trichotillomania (a hair-pulling disorder).